2022
DOI: 10.3390/computers11020020
|View full text |Cite
|
Sign up to set email alerts
|

One View Is Not Enough: Review of and Encouragement for Multiple and Alternative Representations in 3D and Immersive Visualisation

Abstract: The opportunities for 3D visualisations are huge. People can be immersed inside their data, interface with it in natural ways, and see it in ways that are not possible on a traditional desktop screen. Indeed, 3D visualisations, especially those that are immersed inside head-mounted displays are becoming popular. Much of this growth is driven by the availability, popularity and falling cost of head-mounted displays and other immersive technologies. However, there are also challenges. For example, data visualisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 83 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Immersive technologies, both VR and AR, are increasingly being used for immersive analytics [MSD*18] of spatial data [FP21] and abstract data [KFS*22]. Research has shown how the 3D environment can be used as an “immersive space to think” [LDG*21], populating this space with multiple views and representations [RBR22]. However, care must be taken to consider the pitfalls of designing for immersive displays [ML14].…”
Section: Related Workmentioning
confidence: 99%
“…Immersive technologies, both VR and AR, are increasingly being used for immersive analytics [MSD*18] of spatial data [FP21] and abstract data [KFS*22]. Research has shown how the 3D environment can be used as an “immersive space to think” [LDG*21], populating this space with multiple views and representations [RBR22]. However, care must be taken to consider the pitfalls of designing for immersive displays [ML14].…”
Section: Related Workmentioning
confidence: 99%
“…These procedures, which are familiar to the conventional 2D method, are subject to changes and provide new guidelines for producing 3D spatial research (Petrovic, 2003;Hájek et al, 2016). Individual spatial objects (Roberts et al, 2022) are subject to three-dimensional presentation, and a visualization of entire cities is generated (Mao et al, 2020). An increasingly frequent process is the creation of cadastral maps presenting the three-dimensional range of the object's occurrence and the laws of ruling in the form of the 3D cadastre (Aditya et al, 2020;Klapa, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These processes, known in the traditional 2D approach, are subject to modifications and introduce new rules for generating 3D spatial studies (Petrovic, 2003;Hájek et al, 2016). Individual spatial objects (Roberts et al, 2022) are subject to three-dimensional presentation, as well as a visualization of entire cities is generated (Mao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%